Public Administration Reform in Bulgaria: Top-down and Externally-driven Approach - Emilia Zankina (Central European Public Administration Review)
The article examines public administration reform (PAR) in Bulgaria and the main factors that shaped the reform agenda and dynamics. PAR is examined along five key dimensions – transparency and accountability, civil service and human resources management (HRM), public service delivery and digitalisation, organisation and management of government, and policy-making coordination and implementation. The article argues that there are four main factors influencing reform dynamics and determining policy outcomes in the Bulgarian case: the specific political choices made by government elites, external influence of the EU and of past national legacies, and the importance of institutions and reform mechanisms. To illustrate these factors at work, the article examines three policy initiatives, i.e. e-government, the reduction of administrative burden, and civil service reform. The article presents a longitudinal analysis and a qualitative case-study approach, utilising Annual Reports on the Status of the Public Administration 2001–2018, mapping European Semester Documents 2011–2017, an inventory of PAR initiatives 2005–2018, and interviews of public officials. The pushes for reform have been top-down, externally-driven, and stop-and-go in nature. The results confirm previous findings that Bulgaria is among the EU countries with the poorest record in PAR, struggling to overcome communist legacies and high levels of corruption and politicisation. The Bulgarian case highlights several important lessons: the importance of political will and political dynamics for the outcome of reform efforts; the importance of external pressure and financing; the difficulty of uprooting long-standing legacies in administrative traditions; and the limitations of the top-down approach as an obstacle to the sustainability of reform efforts.